Fiber reinforced ceramic composites materials, processing and technology - Mazdiyasni, K. S. (Noyes Publications, 1990)
In this book particular attention is given to the chemistry of sol-gel derived oxide and preceramic polymer derived nonoxide ceramic fibers and matrices, emphasizing their properties and characteristics. Theory, modeling and processing methodologies used for the research and development and manufacturing of advanced structural ceramic composites are included.
Keywords: Fiber-reinforced ceramics.; elektronické knihy; electronic books